THE EFFECTIVENESS OF USING CANVA IN PROJECT-BASED LEARNING TO ENHANCE STUDENTS’ CREATIVITY - Muhammad Dewa Prasetya; Siti Juliana Sari; Selnistia Hidayani (Jurnal Intelek Insan Cendikia, 2025)
This study aims to evaluate the effectiveness of integrating Canva into Project-Based Learning (PjBL) to enhance students’ creativity in language education contexts. Employing a qualitative literature review combined with descriptive analysis, the research synthesizes findings from empirical studies conducted between 2019 and 2025 across various educational levels, ranging from elementary schools to higher education. The reviewed studies utilized diverse instruments such as observation sheets, creativity tests, interviews, and questionnaires to measure indicators of originality, flexibility, elaboration, and collaboration. Results consistently demonstrate that Canva-based PjBL fosters visual creativity by enabling students to transform abstract ideas into concrete digital products, supports collaboration through real-time co-creation features, and increases motivation by providing professional-quality outputs. Quantitative evidence shows significant improvements in creativity scores and learning outcomes, while qualitative findings highlight positive student perceptions of engagement and confidence. The conclusion emphasizes that combining PjBL with Canva creates a pedagogical synergy that strengthens both cognitive and affective dimensions of creativity, preparing learners for the demands of the digital era. The implication for educators is that user-friendly design platforms can be strategically integrated into curricula to cultivate 21st-century skills, though future longitudinal research is recommended to assess long-term impacts on creative retention and professional readiness